Colchicine and SARS-CoV-2: Management of the hyperinflammatory state. (March 2021) - Vitiello, Antonio; Ferrara, Francesco
Abstract: The global COVID-19 pandemic is currently underway. In December 2020, the European Agency of Medicine (EMA) licensed the first Sars-CoV-2 vaccine. Therapeutic management of the COVID-19 positive patient should primarily aim to avoid the severe complications and organ injury caused by generalized inflammation caused by a cytokine storm and occurring in the most severe stages of viral infection. Current knowledge of the pathophysiological mechanisms of SARS- CoV-2 suggests a central role for exaggerated activation of the innate immune system as an important contributor to the adverse outcomes of COVID-19. Several studies have shown that blocking the cytokine storm or acting early with prevention of it can be effective; studies are underway to evaluate agents that may be able to reduce this hyperinflammatory state. The search for effective management strategies for COVID-19 continues to evolve. The actions of colchicine, one of the oldest anti-inflammatory therapies, target multiple targets associated with excessive COVID-19 inflammation. Colchicine is easily administered, generally well tolerated, and inexpensive. This article reports the scientific and molecular rationale for the use of colchicine as monotherapy or in combination in the various stages of SARS-CoV-2 infection to modulate and control the inflammatory state. Low-dose colchicine may be considered safe and effective for the treatment and prevention of cytokine storm in patients with SARS-CoV-2 infection, particularly as an adjunctive remedy to other therapeutic agents. Well-organized clinical studies are needed in this direction. Highlights: The progression of COVID-19 viral infection can be divided into three distinct phases. The actions of colchicine, have multiple targets associated with anti-inflammation. COVID-19-induced cytokine storm can cause multi-organ injury. Colchicine therapy could be considered in all three stages of SARS-CoV-2 infection. Clinical studies are needed.